2016
DOI: 10.1523/eneuro.0130-16.2016
|View full text |Cite
|
Sign up to set email alerts
|

Loss of SynDIG1 Reduces Excitatory Synapse Maturation But Not FormationIn Vivo

Abstract: Modification of the strength of excitatory synaptic connections is a fundamental mechanism by which neural circuits are refined during development and learning. Synapse Differentiation Induced Gene 1 (SynDIG1) has been shown to play a key role in regulating synaptic strength in vitro. Here, we investigated the role of SynDIG1 in vivo in mice with a disruption of the SynDIG1 gene rather than use an alternate loxP-flanked conditional mutant that we find retains a partial protein product. The gene-trap insertion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 30 publications
1
30
0
Order By: Relevance
“…For example, we observed that loss of SynDIG4 leads to increased synapse number similar to that observed in SynDIG1 mutant mice (Chenaux et al, 2016). The increased synapse density observed in SynDIG4 −/− or SynDIG1 mutant mice could be a consequence of reduced synaptic strength.…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…For example, we observed that loss of SynDIG4 leads to increased synapse number similar to that observed in SynDIG1 mutant mice (Chenaux et al, 2016). The increased synapse density observed in SynDIG4 −/− or SynDIG1 mutant mice could be a consequence of reduced synaptic strength.…”
Section: Discussionsupporting
confidence: 76%
“…Second, LTP induced by tetanic stimulation is abolished in both young and adult SynDIG4 −/− mice, while mEPSC amplitudes were reduced by 25% and basal fEPSP transmission was unchanged, which suggests an additional effect of SynDIG4 on synaptic plasticity beyond its role in synapse development. In contrast, such LTP is reduced only in young SynDIG1 mutant mice, likely as a consequence of reduced synaptic transmission (Chenaux et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations